2000
DOI: 10.1074/jbc.m003188200
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin Is a Potent Inducer of Connective Tissue Growth Factor Production via Proteolytic Activation of Protease-activated Receptor-1

Abstract: The coagulation protease thrombin plays a critical role in hemostasis and exerts pro-inflammatory and profibrotic effects via proteolytic activation of the major thrombin receptor, protease-activated receptor-1 (PAR-1). Connective tissue growth factor (CTGF) is a novel fibroblast mitogen and also promotes extracellular matrix protein production. It is selectively induced by transforming growth factor ␤ (TGF-␤) and is thought to be the autocrine agent responsible for mediating its pro-fibrotic effects. CTGF is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
172
0
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(181 citation statements)
references
References 46 publications
(50 reference statements)
5
172
0
4
Order By: Relevance
“…Coagulation cascade activation is a prominent feature of both acute and chronic inflammatory processes. Several reports support the hypothesis of a key role for coagulation factors in the pathogenesis of tissue fibrosis, particularly within the kidney (8,(27)(28)(29)(30). Interestingly, earlier works suggested that FXa, the enzymatically active constituent of the prothrombinase complex, triggers complex pathways involved in the regulation of cellular growth (31,32).…”
mentioning
confidence: 93%
“…Coagulation cascade activation is a prominent feature of both acute and chronic inflammatory processes. Several reports support the hypothesis of a key role for coagulation factors in the pathogenesis of tissue fibrosis, particularly within the kidney (8,(27)(28)(29)(30). Interestingly, earlier works suggested that FXa, the enzymatically active constituent of the prothrombinase complex, triggers complex pathways involved in the regulation of cellular growth (31,32).…”
mentioning
confidence: 93%
“…Regulators such as VEGF, S1P, and hypoxia-inducible factor (HIF)-1a have been reported to induce CCN2 production in different cells (26)(27)(28). CCN2 is also upregulated by other fibrogenetic cytokines including angiotension II, endothelin 1, and thrombin (29)(30)(31). On the other hand, epigenetic silencing by hypermethylation of the CCN2 promoter leads to a loss of CCN2 function, which may be a causative factor in the carcinogenesis of ovarian cancer (32).…”
Section: Introductionmentioning
confidence: 99%
“…8 -10 In addition to endogenous proteases, PARs can be selectively activated by short agonistic peptides (PAR-AP) that cor-respond to the tethered ligand exposed after PAR 1 and PAR 2 cleavage. 9,10 Studies with these agonists, as well as with PAR 1 -deficient mice, have led to the conclusion that PAR 1 is the major receptor responsible for mediating most of the proinflammatory and profibrotic effects 17 of thrombin.…”
mentioning
confidence: 99%
“…18 -24 Thrombin might be mechanistically involved in regulating hepatic fibrogenesis. 5,17 Even though thrombin expression is increased in cirrhotic patients 5 and exposure of HSCs to thrombin triggers a number of effector functions, including proliferation, contraction, and collagen synthesis, 21,22 the functional relevance of PAR 1 in modulating HSC activity and collagen deposition in vivo is unknown. Fig.…”
mentioning
confidence: 99%